APLIKASI HIPNOSIS (Tinjuan Komunikasi Dakwah) - Meisil B Wulur (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
This paper explains about the Hipnos Application, which is reviewed through Da'wah communication. Hypnosis is a communication method using an effective communication approach, which has a role in influencing clients in the hypnosis process. So the da'wah messages conveyed in the hypnosis application can be conveyed, and received by the client as mad, and communicant. This study aims to find out what form of communication in hypnosis applications.